2010
DOI: 10.1016/j.bone.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic loci for bone architecture determined by three-dimensional CT in crosses with the diabetic GK rat

Abstract: The F344 rat carries alleles contributing to bone fragility while the GK rat spontaneously develops type-2 diabetes. These characteristics make F344 x GK crosses well suited for the identification of genes related to bone size and allow for future investigation on the association with type-2 diabetes. The aim of this study was to identify quantitative trait loci (QTLs) for bone size phenotypes measured by a new application of three-dimensional computed tomography (3DCT) and to investigate the effects of sex-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Several QTLs identified in this study co-localized with our previously reported QTLs linked to tibial bone phenotypes obtained from pQCT and 3D CT [23], [24] and were in many cases influenced by sex- and reciprocal cross (Table 4). The region on chromosome 1 (17–79 cM) linked to multiple phenotypes obtained from all four methods (pQCT, 3D CT, 3PB and DXA) in both males and females showed predominantly higher significance in the reciprocal cross 1 carrying GK mtDNA.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Several QTLs identified in this study co-localized with our previously reported QTLs linked to tibial bone phenotypes obtained from pQCT and 3D CT [23], [24] and were in many cases influenced by sex- and reciprocal cross (Table 4). The region on chromosome 1 (17–79 cM) linked to multiple phenotypes obtained from all four methods (pQCT, 3D CT, 3PB and DXA) in both males and females showed predominantly higher significance in the reciprocal cross 1 carrying GK mtDNA.…”
Section: Discussionsupporting
confidence: 76%
“…Previously, we reported results from a genome-wide screen for bone size and trabecular and cortical bone structure of tibia in the same F2 progeny [23], [24]. The biomechanical testing reported here provides bone phenotypes directly reflecting the ability of bone to resist fracture.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations